Efficiency of the application of automotive liquid reducer agent (arla-32) as a nitrogen foliage fertilizer in pasture (Research, Society and Development, 2022)
Nitrogen fertilization plays an important role in forage grass productivity. Foliar N fertilization aims to complete the fertilization by the soil and Arla32 is considered as a foliar source of Nitrogen. This research aims to evaluate the effectiveness of the product and was carried out in the experimental area of ​​the Agronomy Course on the UNITPAC Campus, in Araguaína-TO. The variable evaluated was the dry matter increment through the analysis of 3 doses of Arla, 1 dose of a commercial foliar fertilizer based on 30% of Nitrogen and untreated control, with 4 replications each. The treatment performed with foliar fertilizer presented the best yields, while the treatments with Arla presented better results than the untreated control, but statistically equal.